2006
DOI: 10.2527/2006.8461403x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the inclusion of soybean oil and soybean processing by-products to soybean meal on nutrient composition and digestibility in swine and poultry

Abstract: This experiment was designed to evaluate the effects of selected soybean (SB) processing byproducts (gums, oil, soapstock, weeds/trash) when added back to soybean meal (SBM) during processing on the resulting nutrient composition, protein quality, nutrient digestibility by swine, and true metabolizable energy (TMEn) content and standardized AA digestibility by poultry. To measure ileal DM and nutrient digestibility, pigs were surgically fitted with a T-cannula in the distal ileum. The concentration of TMEn and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…Several soya products are used in poultry feeding, including soya bean meal (SBM), fullfat soya bean (FFSB) and soya protein concentrate (SPC). Bruce et al (2006) have observed that the digestibility of AA was reduced when SBM was substituted by FFSB in poultry diets. In contrast, Valencia et al (2008b) have not found any effect on CIAD of CP and AA when FFSB was replaced by an equivalent amount of SBM and soya bean oil in piglet diets.…”
Section: Introductionmentioning
confidence: 96%
“…Several soya products are used in poultry feeding, including soya bean meal (SBM), fullfat soya bean (FFSB) and soya protein concentrate (SPC). Bruce et al (2006) have observed that the digestibility of AA was reduced when SBM was substituted by FFSB in poultry diets. In contrast, Valencia et al (2008b) have not found any effect on CIAD of CP and AA when FFSB was replaced by an equivalent amount of SBM and soya bean oil in piglet diets.…”
Section: Introductionmentioning
confidence: 96%
“…In many countries, soybean meal (SBM) is the main protein-based ingredient used in pig diets, because of its high protein content (44% to 49%), suitable EAA profile (Bruce et al, 2006) and high SID EAA (NRC, 2012). For example, the Lys SID is higher for SBM (89% to90%) than for rapeseed meal (RSM) (78%) and cottonseed meal (CSM) (64%).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean soapstock (SS) is a byproduct of the crude soybean oil (CSO) extraction and, if the SS is properly processed, it can be added to animal feed (Bruce et al, 2006;Dumont & Narine, 2007). This byproduct is a cheap source of energy and can be used in pig diets because its cost can be up to half of the CSO.…”
Section: Introductionmentioning
confidence: 99%